2016
DOI: 10.1016/j.stemcr.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Induced Oxidative Stress Reduces Proliferation in Embryonic Stem Cells via FOXO3A/β-Catenin-Dependent Transcription of p21cip1

Abstract: SummaryEmbryonic stem cells (ESCs), which are derived from a peri-implantation embryo, are routinely cultured in medium containing diabetic glucose (Glc) concentrations. While pregnancy in women with pre-existing diabetes may result in small embryos, whether such high Glc levels affect ESC growth remains uncovered. We show here that long-term exposure of ESCs to diabetic Glc inhibits their proliferation, thereby mimicking in vivo findings. Molecularly, Glc exposure increased oxidative stress and activated Fork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 44 publications
4
63
1
Order By: Relevance
“…We next considered the impact of DAC treatment on gene expression. CDKN1A and CDKN1B are targeted by FOXO3A [ 30 ] and are downregulated in a variety of tumors. As shown in Figure 2(c) , protein expression of both of these genes was rare in untreated SKM-1 cells, but increased after DAC treatment, especially CDKN1A ( P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…We next considered the impact of DAC treatment on gene expression. CDKN1A and CDKN1B are targeted by FOXO3A [ 30 ] and are downregulated in a variety of tumors. As shown in Figure 2(c) , protein expression of both of these genes was rare in untreated SKM-1 cells, but increased after DAC treatment, especially CDKN1A ( P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…FOXO3a is a central transcription factor that mediates multiple physiological and pathological processes by inducing transcription of target genes involved in apoptosis [ 62 ], proliferation [ 63 ], cell cycle progression [ 64 ], survival [ 65 ] and DNA damage [ 66 ] (Fig. 2 ).…”
Section: Overview: Structure Regulation and Function Of Foxo3amentioning
confidence: 99%
“…Previous reports investigating the effects of high glucose on stem cell functions are controversial as there are differing perspectives. For example, some studies have shown that high glucose induces senescence and apoptosis in stem cells [1, 4, 5]. Conversely, other studies have shown that high glucose stimulates proliferation and enhances osteogenic differentiation potential in mesenchymal stem cells (MSCs) [6].…”
Section: Introductionmentioning
confidence: 99%